0398 The Therapeutic Relationship Matters: Working Alliance Quality as a Predictor of Post-Treatment Insomnia Severity in Cognitive-Behavioral Therapy for Insomnia (CBT-I). (27th April 2018) - Robertson, K; Mogharreban, N; Seeman, S; Simpson, N; Asarnow, L; Rangel, E; Manber, R
Abstract: Introduction: Prior research has shown that the therapeutic alliance is a contributor to change in general psychotherapy and in group psychotherapy for insomnia. Little is known about how the patient-rated quality of the working alliance relates to insomnia severity outcomes in individual Cognitive-Behavioral Therapy for Insomnia (CBT-I). Methods: This study included data from 64 participants who were randomized to and completed five sessions of CBT-I during pregnancy as part of a randomized controlled study of perinatal insomnia. Participants were pregnant women (mean age=33.9, SD=4.5) with insomnia disorder, not receiving other treatments for insomnia. Measures included the Insomnia Severity Index (ISI), completed at pre- (mean=15.5, SD=4.3) and post-treatment (within two weeks after Session 5, mean=7.6, SD=5.0). Participants completed the Working Alliance Inventory-Short Revised (WAI-SR) form following Session 2, and the total score was calculated to measure working alliance quality (mean=75.6, SD=9.2). Results: A two-stage hierarchical multiple regression analysis demonstrated that, after adjusting for pre-treatment insomnia severity scores, the quality of the working alliance was a significant predictor of insomnia severity scores at post-treatment (F(2, 61)=5.79, p<.005) and accounted for 11.7% of the variance. There was a positive relationship between pre- and post-treatment insomnia severity (β=.246) and a negative relationship between working alliance quality and post-treatment insomnia severity (β=-.344). Conclusion: A higher quality working alliance predicted lower insomnia severity rating at post-treatment in individual CBT for perinatal insomnia. A limitation of this study is its generalizability to populations with insomnia that are not pregnant women. Nonetheless, the results suggest that cultivating a high quality working alliance enhances clinical outcomes even within a short-term, skills-based treatment such as CBT-I. Support (If Any): NR013662.